The Macroeconomic Effects of Labor and Product Market Reforms in Morocco - Sarr, Babacar (IMF Working Papers; Working Paper ;, 2019)
This paper studies the macroeconomic effects and sequencing of (LMRs) and product (PMRs) market reforms in Morocco. It finds that introducing LMRs and PMRs simultaneously would add about 2.5 percentage points (pp) of GDP growth and reduce unemployment by about 2.2 pp after five years. If sequencing is required, starting with PMRs would be more effective in boosting output, while starting with LMRs would reduce unemployment faster. Finally, increasing unemployment benefits would be more effective if this reform takes place after the implementation of LMRs and PMRs.